Menikah di Tengah Studi: Menikah di Tengah Studi: Menilik Praktik Pada Mahasiswa Hukum Keluarga Islam UIN Raden Intan Lampung - Adri Latif (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
Examining the phenomenon of marriage in the middle of study in Islamic Family Law students at UIN Raden Intan Lampung with a focus on the discussion on the reasons students get married in the middle of study, this study uses Max Weber's Social Action theory with the concept of the Verstehen approach. This research attempts to explore the reasons behind Islamic Family Law students at UIN Raden Intan getting married in the middle of their studies. The author used interviews as a data collection technique which was conducted on 6 informants (3 pairs) presented with analytic descriptive method. The results found that the reason students decided to get married was due to encouragement from their parents and because they had wanted to get married for a long time. Regarding lecture activities, no significant obstacles were encountered. The enthusiasm to finish college remains burning even though the status is already a wife. Keyword: Marriage, Recommendation, Religion